Plant engineer's handbook - Mobley, R. Keith, 1943- (Boston : Butterworth-Heinemann, 2001)
Plant engineers are responsible for a wide range of industrial activities, and may work in any industry. This means that breadth of knowledge required by such professionals is so wide that previous books addressing plant engineering have either been limited to only certain subjects or cursory in their treatment of topics. The Plant Engineering Handbook offers comprehensive coverage of an enormous range of subjects which are of vital interest to the plant engineer and anyone connected with industrial operations or maintenance. This handbook is packed with indispensable information, from defining just what a Plant Engineer actually does, through selection of a suitable site for a factory and provision of basic facilities (including boilers, electrical systems, water, HVAC systems, pumping systems and floors and finishes) to issues such as lubrication, corrosion, energy conservation, maintenance and materials handling as well as environmental considerations, insurance matters and financial concerns. One of the major features of this volume is its comprehensive treatment of the maintenance management function; in addition to chapters which outline the operation of the various plant equipment there is specialist advice on how to get the most out of that equipment and its operators. This will enable the reader to reap the rewards of more efficient operations, more effective employee contributions and in turn more profitable performance from the plant and the business to which it contributes. The Editor, Keith Mobley and the team of expert contributors, have practiced at the highest levels in leading corporations across the USA, Europe and the rest of the world. Produced in association with Plant Engineering magazine, this book will be a source of information for plant engineers in any industry worldwide. * A Flagship reference work for the Plant Engineering series * Provides comprehensive coverage on an enormous range of subjects vital to plant and industrial engineer * Includes an international perspective including dual units and regulations.
Definition and organization of the plant engineering function / Richard Dunn -- Plant engineering in Britain / Roger S Pratt -- The role of the plant engineer / R Keith Mobley -- Physical considerations in site selection / D Whittleton -- Plant location / Barry Holmes -- Industrial buildings / D Whittleton -- Planning and plant layout / Roland R Gibson -- Contracts and specifications / Ken Taylor -- Industrial flooring / JDN Shaw -- Lighting / Hugh King -- Insulation / FT Gallyer -- Paint coatings for the plant engineer / DA Bayliss -- Insurance : plant and equipment / AP Hyde -- Insurance : buildings and risks / Risk Control Unit -- Electricity generation / IG Crow and K Shippen -- Electrical distribution and installation / IG Crow and R Robinson -- Electrical instrumentation / H Barber -- Oil / Roland Gibson -- Gas / Peter F Fleming -- Liquefied petroleum gas / RH Shipman -- Coal and ash / R Keith Mobley -- Steam utilization / Albert Armer -- Industrial boilers / E Walker and RJ Blaen -- Combustion equipment / Colin French -- Economizers / Colin French -- Heat exchangers / Brian R Lamb -- Heating / GE Pritchard -- Ventilation / PD Compton -- Air conditioning / J Bevan -- Energy conservation / MG Burbage-Atter -- Water and effluents / George Solt -- Pumps and pumping / Keith Turton -- Centrifugal pump installation / John Neller -- Compressed air systems / British Compressed Air Society -- Compressors / R Keith Mobley -- Fans and blowers / R Keith Mobley -- Mixers and agitators / R Keith Mobley -- Gears and gearboxes / R Keith Mobley -- Hydraulic fundamentals / R Keith Mobley -- Pneumatic fundamentals / Roger C Webster -- Vibration fundamentals / R Keith Mobley -- Vibration monitoring and analysis / R Keith Mobley -- Air pollution / Roger C Webster -- Dust and fume control / Brian Auger -- Dust collection systems / R Keith Mobley -- Maintenance management in UK / George Pitblado -- Effective maintenance management / Ricky Smith -- Predictive maintenance / R Keith Mobley -- Planning and scheduling outages / Ricky Smith -- Lubrication / Stuart McGrory -- Corrosion / Michael J Schofield -- Shaft alignment / R Keith Mobley -- Rotor balancing / R Keith Mobley -- Packing and seals / R Keith Mobley -- Gears and gear drives / R Keith Mobley -- Flexible intermediate drives / R Keith Mobley -- Couplings and clutches / R Keith Mobley -- Bearings / R Keith Mobley -- Finance for the Plant Engineer / Leon Turrell -- Statistical approaches in machinery problem solving / Ricky Smith -- Health and safety in the UK / George Pitblado -- Regulatory compliance issues in the US / R Keith Mobley.
Includes index.
Keywords: Plant engineering -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc